The Development of Green Energy Policy Planning Model to Improve Economic Growth in Indonesia - Daryono, Daryono; Wahyudi, Sugeng; Suharnomo, Suharnomo (International Journal of Energy Economics and Policy, 2019)
Energy is an element that is vital in everyday life. Its use continues to increase along with the increasing demand for energy which is influenced by population growth and economic growth. Until now, energy use is still dominated by the depletion of fossil energy, while its management is still not optimal. Energy planning needs to be done as the basis of a government policy in managing energy in order to realize national energy independence and security. This paper focuses on achieving the use of new and renewable energy according to the target of the National Energy Policy in 2025 in Java Island. Energy planning is carried out using the Computable General Equilibrium (CGE) model approach, which is an approach that can illustrate the balance between energy supply and needs. Simulations are made in the Green Energy (GREN) scenario by including several key parameters for the year of projections 2016-2025. The simulation results show an increase in the percentage of new and renewable energy use in the energy mix in 2025 by 12%. This explains that the target of National Energy Policy towards the use of new and renewable energy is reached, which is equal to 23%. Keywords: green energy, projection, LEAP, new and renewable, CGE. JEL Classifications: P18, Q43, Q47, Q48 DOI: https://doi.org/10.32479/ijeep.7779